Penerapan Strategi Promotion Mix di Dream Max Cleaning Shoes - Candy Candy; Ade Agustika Br Surbakti (ConCEPt - Conference on Community Engagement Project, 2021)
This practical work was carried out to develop the extent of the marketing mix (promotion mix) at Dream Max Cleaning Shoes, namely in terms of Advertising, Direct Marketing, and Sales Promotion. This practical work was carried out to find out how to advance the marketing mix strategy. The problem in this activity is how Dream Max can increase the profit of selling its services and also expand the target market to increase brand awareness which aims to introduce the services it has. This activity is classified as field research using data collection techniques using primary and secondary data that have been collected through direct interviews, observation, documentation, and by collecting various references through websites and related journals. Using the discussion method, namely the qualitative descriptive analysis method, is the writing of data by separating the data that has been collected so far by grouping the data and being able to present it in a paper on the basis of existing theories and data that has been collected and is in accordance with the facts and facts. -fact. From the results that have been implemented through Instagram advertising, banners, loyalty cards, and feedback telemarketing using the WhatsApp application, it has increased insight impressions that are very high than before and succeeded in increasing revenue and also succeeded in expanding its target market. The results that can be taken from this practical work activity are the promotion mix strategy is very important for the sustainability of Dream Max Cleaning Shoes so that they can continue to provide the best services in the future.